Quantification of organ motion during chemoradiotherapy of rectal cancer using cone-beam computed tomography. - Chong, I; Hawkins, M; Hansen, V; Thomas, K; McNair, H; O'Neill, B; Aitken, A; Tait, D (2011)
PURPOSE: There has been no previously published data related to the quantification of rectal motion using cone-beam computed tomography (CBCT) during standard conformal long-course chemoradiotherapy. The purpose of the present study was to quantify the interfractional changes in rectal movement and dimensions and rectal and bladder volume using CBCT and to quantify the bony anatomy displacements to calculate the margins required to account for systematic (Σ) and random (σ) setup errors. METHODS AND MATERIALS: CBCT images were acquired from 16 patients on the first 3 days of treatment and weekly thereafter. The rectum and bladder were outlined on all CBCT images. The interfraction movement was measured using fixed bony landmarks as references to define the rectal location (upper, mid, and low), The maximal rectal diameter at the three rectal locations was also measured. The bony anatomy displacements were quantified, allowing the calculation of systematic (Σ) and random (σ) setup errors. RESULTS: A total of 123 CBCT data sets were analyzed. Analysis of variance for standard deviation from planning scans showed that rectal anterior and lateral wall movement differed significantly by rectal location. Anterior and lateral rectal wall movements were larger in the mid and upper rectum compared with the low rectum. The posterior rectal wall movement did not change significantly with the rectal location. The rectal diameter changed more in the mid and upper than in the low rectum. No consistent relationship was found between the rectal and bladder volume and time, nor was a significant relationship found between the rectal volume and bladder volume. CONCLUSIONS: In the present study, the anterior and lateral rectal movement and rectal diameter were found to change most in the upper rectum, followed by the mid rectum, with the smallest changes seen in the low rectum. Asymmetric margins are warranted to ensure phase 2 coverage.